2023
DOI: 10.1111/jpi.12931
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a chronobiotic/cytoprotective agent in bone. Doses involved

Daniel P. Cardinali

Abstract: Because the chronobiotic and cytoprotective molecule melatonin diminishes with age, its involvement in postmenopausal and senescence pathology has been considered since long. One relevant melatonin target site in aging individuals is bone where melatonin chronobiotic effects mediated by MT1 and MT2 receptors are demonstrable. Precursors of bone cells located in bone marrow are exposed to high quantities of melatonin and the possibility arises that melatonin acts a cytoprotective compound via an autacoid effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…In studies focusing on the chronobiotic effect, lower doses of melatonin were found to be effective. However, the impact of melatonin on bone occurs through a distinct pathway from that of the receptors involved in its chronobiotic effect [ 16 , 22 , 61 ]. It has been observed that higher doses of melatonin are required to have an impact on bone remodelling [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In studies focusing on the chronobiotic effect, lower doses of melatonin were found to be effective. However, the impact of melatonin on bone occurs through a distinct pathway from that of the receptors involved in its chronobiotic effect [ 16 , 22 , 61 ]. It has been observed that higher doses of melatonin are required to have an impact on bone remodelling [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the strongest known antioxidants [ 13 ], melatonin, is a hormone synthesised in the pineal gland [ 15 ]. It can be demonstrated that it has both chronobiotic and cytoprotective functions [ 16 ]. Melatonin is crucial in regulating the daily biorhythm, [ 14 ] immunity, and sleep [ 15 ]; it also has antioxidant [ 13 ] and anti-inflammatory [ 17 ] effects.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations